AUV Swarm Confrontation Search Method Based on the MADDPG Algorithm - An, Ruiqi; Li, Le; Bai, Miao; Zhang, Pu; Guo, Zhaozhi; Zuo, Ri (Chinese Control and Decision Conference, 2025)
In this paper, an Autonomous Underwater Vehicle (AUV) swarm confrontation search method based on the Multi-Agent Deep Deterministic Policy Gradient (MADDPG) algorithm is proposed for the AUV swarm confrontation search problem. Firstly, the AUV swarm confrontation search model is constructed. Secondly, the multiagent state space, action space, observation space, and reward function are designed for the AUV swarm confrontation search problem, and the MADDPG algorithm is adopted to obtain the AUV swarm confrontation search method. Finally, the effectiveness and the generality of the proposed AUV swarm confrontation search method are verified by simulation experiments for the AUV swarm confrontation search tasks under different speed conditions and sonar detection distances.